Chemoselective Organoclick–Click Sequence - Belkheira, Mokhtaria; El Abed, Douniazad; Pons, Jean-Marc; Bressy, Cyril (Synthesis, 2018)
A highly chemoselective bis-triazole synthesis based on a sequence organocatalyzed click reaction/copper-catalyzed click reaction is described in this paper. A range of bis-azides react with various ketones using proline catalysis through the aryl azide moiety while the alkyl azide one remains available for a metal-catalyzed triazole synthesis.
Keywords: triazoles; organocatalysis; organoclick reaction; click reaction; chemoselectivity